Comparison of Spread Spectrum with Redundant Pattern Coding In Securing Text Messages Into Audio: Comparison of Spread Spectrum with Redundant Pattern Coding In Securing Text Messages Into Audio - Ray Sanjaya Gulo; Reni Lusiana Simangunsong; Stephen Boy Kristian Tafonao; Muhammad Yusuf; Yennimar Yennimar (Jurnal Mantik, 2020)
The transmission of information from one place to another is mostly constrained by the security problems of the information itself. Moreover, this information is very confidential, so not just anyone can open it. One of the ways that can be done to hide confidential information is by using cryptographic techniques, namely by encoding the information using certain algorithms. The second way is to insert the information into certain media, such as digital images or audio, so that the information will be hidden and what will appear is the media only, while the information is disguised. In this study, the comparison of the Spread Spectrum steganography algorithm with the Redundant Pattern Coding algorithm to secure text messages in audio files. The data used are audio files with a size between 200 Kb to 265 Kb and text with a size of 50 bytes to 275 bytes. The experimental results obtained stego audio files from the insertion of the Spread Spectrum algorithm with an average PSNR value of 41,138 db and for the Redundant Pattern Coding algorithm the average PSNR value was 29,885 db.